THE IMPLEMENTATION OF TASK BASED INSTRUCTION IN TEACHING ESP : A Qualitative Study of Language Teaching Method in One of Sekolah Bahasa in Bandung - Susan, Ivonne (2016)
This study investigates how task based instruction (TBI) was implemented in ESP classroom and the advantages and limitation in applying TBI in ESP classroom. It is a Qualitativeresearch, the research was conducted in one of Sekolah Bahasa in Bandung. The study involved 27aircraft engineering students of a higher education and a teacher as participants. The data were collected through observation, questionnaireand interview. The data from the observation, interview, and questionnairewere gained to show how TBI was implemented in ESP classroom, and were analysed to reveal the advantages and the limitation of implementing TBI in ESP classroom. The study revealed that TBI promoted learning by doing, promoted communicative learning, improved students' participation in the classroom, focused on meaning and form, and improved students' speaking skill. The limitation in applying TBI in ESP classroom covered time availability and the number of the students.